Inter-laboratory study for the certification of trace elements in seawater certified reference materials NASS-7 and CASS-6 - Yang, Lu; Nadeau, Kenny; Meija, Juris; Grinberg, Patricia; Pagliano, Enea; Ardini, Francisco; Grotti, Marco; Schlosser, Christian; Streu, Peter; Achterberg, Eric P; Sohrin, Yoshiki; Minami, Tomoharu; et al. (Analytical and bioanalytical chemistry, 2018)
Certification of trace metals in seawater certified reference materials (CRMs) NASS-7 and CASS-6 is described. At the National Research Council Canada (NRC), column separation was performed to remove the seawater matrix prior to the determination of Cd, Cr, Cu, Fe, Pb, Mn, Mo, Ni, U, V, and Zn, whereas As was directly measured in 10-fold diluted seawater samples, and B was directly measured in 200-fold diluted seawater samples. High-resolution inductively coupled plasma mass spectrometry (HR-ICPMS) was used for elemental analyses, with double isotope dilution for the accurate determination of B, Cd, Cr, Cu, Fe, Pb, Mo, Ni, U, and Zn in seawater NASS-7 and CASS-6, and standard addition calibration for As, Co, Mn, and V. In addition, all analytes were measured using standard addition calibration with triple quadrupole (QQQ)-ICPMS to provide a second set of data at NRC. Expert laboratories worldwide were invited to contribute data to the certification of trace metals in NASS-7 and CASS-6. Various analytical methods were employed by participants including column separation, co-precipitation, and simple dilution coupled to ICPMS detection or flow injection analysis coupled to chemiluminescence detection, with use of double isotope dilution calibration, matrix matching external calibration, and standard addition calibration. Results presented in this study show that majority of laboratories have demonstrated their measurement capabilities for the accurate determination of trace metals in seawater. As a result of this comparison, certified/reference values and associated uncertainties were assigned for 14 elements in seawater CRMs NASS-7 and CASS-6, suitable for the validation of methods used for seawater analysis.
Keywords: Standard addition calibration; HR-ICPMS; Seawater; Certified reference material; Dissolved trace metals; Flow injection analysis; Isotope dilution